Comparative efficacy and safety of infliximab biosimilar (BCD-055) and innovator infliximab in patients with ankylosing spondylitis (results of international, multiple-center, double-blind phase I and phase III clinical studies) - D. E. Karateev; V. I. Mazurov; E. V. Zonova; O. B. Nesmeyanova; T. V. Plaksina; D. G. Krechikova; O. V. Reshetko; L. N. Denisov; I. G. Gordeev; T. G. Pokrovskaya; O. V. Antipova; T. V. Kropotina; et al. (Современная ревматология, 2017)
This article presents results from two clinical trials of infliximab biosimilar, BCD-055, including comparative data on the pharmacokinetics (PK), efficacy and safety of BCD-055 and innovator infliximab (IFX) in patients with ankylosing spondylitis (AS).Objective: The purpose of phase I clinical study ASART-1 was to evaluate the pharmacokinetic and safety profile of BCD-055 and to prove its equivalence with Remicade®, phase III study ASART-2 was conducted to evaluate the efficacy and tolerability of BCD-055 in comparison with Remicade® in patients with active AS.Patients and methods: Both studies were conducted as international multi-center randomized double-blind studies in direct comparison with innovator IFX. Inclusion and exclusion criteria, main examination methods, and drug regimens were the same in both trials. A total of 199 patients were enrolled in the studies. After the screening, the patients were stratified by CRP and BASDAI score, randomized (1:1 ratio in ASART-1; 2:1 ratio in ASART-2) into 2 arms and received BCD-055 or innovator IFX at a dose 5 mg/kg IV at 0, 2, 6 and then every 8 weeks (up to week 54). The primary endpoint for PK profile evaluation was the area under the concentration-time curve (AUC(0-tau)), maximum serum concentration of infliximab at steady state Cmax,ss. Efficacy was assessed by achieving ASAS20 at week 30, the endpoints for safety profile were the incidence of adverse events and serious adverse events during the maintenance-dosing phase and withdrawals from the study due to the safety reasons.Results: A total of 81 patients (ASART-1 study) were included in PK analysis, 199 patients were in efficacy and safety analysis. AUC(0-tau) value were 25,420,996.25±11,635,015.74 (ng/ml) Cmax,ss for BCD-055 and 26,114,705.71±12,102,376.9 (ng/ml)⋅h for INF innovator (p>0.05). Cmax,ss for BCD-055/Remicade® was 122,752 [99,401–151,553] ng/ml and 119,844 [98,120–132,772] ng/ml, respectively (p>0.05). ASAS20 was achieved at week 30 by 81.30% of the patients in the BCD-055 group, and 67.74% in the INF innovator group (p=0.061). The analysis of secondary endpoints (BASDAI, BASMI, BASFI, MASES, quality of life, chest excursion, and number of pathologically changed joints) showed no difference between the biosimilar and innovator groups. BCD-055 and innovator IFX showed highly similar safety profiles in both studies without cases of unexpected toxicity. The rates of AEs were equivalent for both drugs and were 48.48% and 58.21% of patients in the BCD-055 and Remicade®, respectively.Conclusion: BCD-055 is found to be equivalent in terms of PK, and showed the similarity in efficacy and safety profile compared with innovator IFX in patients with active AS.